Thrombectomy with the pRESET vs solitaire stent retrievers as first-line large vessel occlusion stroke treatment: a randomized clinical trial - Nogueira, Raul G.; Lobsien, Donald; Klisch, Joachim; Pielenz, Daniel; Lobsien, Elmar; Sauvageau, Eric; Aghaebrahim, Nima; Möhlenbruch, Markus Alfred; Vollherbst, Dominik; Ulfert, Christian; Bozorgchami, Hormozd; Clark, Wayne; et al. (JAMA neurology, 2024)
Stent retriever-based thrombectomy is highly beneficial in large vessel occlusion (LVO) strokes. Many stent retriever designs are currently available, but comparison of these technologies in well-conducted studies is lacking.To determine whether thrombectomy for LVO stroke with the pRESET stent retriever is noninferior to treatment with the Solitaire stent retriever.This study was a multicenter, prospective, randomized, controlled, open-label, adaptive, noninferiority trial with blinded primary end point evaluation. Between October 2019 and February 2022, multicenter participation occurred across 19 research hospitals and/or universities in the US and 5 in Germany. Patients with LVO stroke were enrolled and included up to 8 hours after symptom onset.Patients underwent 1:1 randomization to thrombectomy with the pRESET or Solitaire stent retriever.The primary outcome was the difference in the rate of 90-day functional independence across the 2 devices, using a −12.5% noninferiority margin for the lower bound of the 1-sided 95% CI of the difference between pRESET and Solitaire retrievers.Of 340 randomized patients, 170 (50.0%) were female, and the median (IQR) age was 73.0 (64.0-82.0) years. The study procedure was completed in 322 of the 340 randomized patients. The primary end point of 90-day functional independence was achieved by 95 patients (54.9%; 95% CI, 48.7-61.1) in the pRESET group and in 96 (57.5%; 95% CI, 51.2-63.8) in the Solitaire group (absolute difference, −2.57%; 95% CI, −11.42 to 6.28). As the lower bound of the 95% CI was greater than −12.5%, the pRESET retriever was deemed noninferior to the Solitaire retriever. The noninferiority of pRESET over Solitaire was also observed in the secondary clinical end point (90-day shift in modified Rankin Scale score) and in both angiographic end points (Expanded Treatment in Cerebral Infarction [eTICI] score of 2b50 or greater within 3 passes: 146 of 173 [84.4%] vs 149 of 167 [89.2%]; absolute difference, −4.83%; 95% CI, −10.84 to 1.19; eTICI of 2c or greater following the first pass: 76 of 173 [43.7%] vs 74 of 167 [44.3%]; absolute difference, −0.63%; 95% CI, −9.48 to 8.21). Symptomatic intracranial hemorrhage occurred in 0 patients in the pRESET group and 2 (1.2%) in the Solitaire group. Mortality occurred in 25 (14.5%) in the pRESET group and in 24 (14.4%) in the Solitaire group at 90 days. Findings of the per-protocol and as-treated analyses were in concordance with findings of the intention-to-treat analysis.In this study, among patients with LVO stroke, thrombectomy with the pRESET stent retriever was noninferior to thrombectomy with the Solitaire stent retriever. Findings suggest that pRESET offers a safe and effective option for flow restoration and disability reduction in patients with LVO stroke.
Published online January 2, 2024. Corrected on February 12, 2024
Gesehen am 18.12.2024